New species of Scalibregmatidae (Annelida) from slope and abyssal depths off eastern Australia - Blake, James A. (Records of the Australian Museum, 2023)
Seven new species of Scalibregmatidae are described from deep waters off the east coast of Australia. Samples were collected as part of the RV Investigator voyage IN2017_V03 in May/June 2017 using a Brenke sledge and 0.25 m2 box core. Sample depths reported in the present study were from the lower continental slope of about 2450 m to abyssal depths up to 4280 m. These collections provide the first scalibregmatid polychaetes to be described from deep water off Australia. The new species of Scalibregmatidae are in the genera Asclerocheilus (1), Axiokebuita (1), Oligobregma (4), and Pseudoscalibregma (1). Each of the new species is compared and contrasted with their known congeners. Asclerocheilus and Oligobregma are the largest genera of the family in terms of numbers of species; the known species of each of these genera are tabulated and compared. The Scalibregmatidae known from abyssal depths of about 3000 m and greater are reviewed and discussed.
World Polychaeta Database (WPolyD).